2004
DOI: 10.1002/jbm.b.30111
|View full text |Cite
|
Sign up to set email alerts
|

FTIR study of carbonate loss from carbonated apatites in the wide temperature range

Abstract: The mineral constituent of bone tissue is a carbonate-substituted apatite (CHA). The thermal stability of the CHA has been revealed to depend on the substitution type and degree, although relatively little is known about this behavior. The aim of this study was to investigate the carbonate loss from synthetic CHAs in equilibrium conditions in a wide temperature range. An approach based on FTIR spectroscopy of condensed gas phase was applied to evaluate the CO and CO2 release with increasing temperature. Four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…As the rate of mass loss (DTG=dm/dT) showed, about 5wt% was lost up to 550 C and the remainder up to 950 C. Such a mass loss in hydroxyapatite was observed earlier and usually associated with the loss of adsorbed water in the lower temperature range and of carbon dioxide above 550 C [5][6][7][8]. However, the mass loss below 550 C was also related to the release of structural water [6,10].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As the rate of mass loss (DTG=dm/dT) showed, about 5wt% was lost up to 550 C and the remainder up to 950 C. Such a mass loss in hydroxyapatite was observed earlier and usually associated with the loss of adsorbed water in the lower temperature range and of carbon dioxide above 550 C [5][6][7][8]. However, the mass loss below 550 C was also related to the release of structural water [6,10].…”
Section: Resultsmentioning
confidence: 91%
“…An easy way to introduce impurities is the conventional precipitation method. However, success in this way was limited because the role of incorporated counter-ions of parent compounds in the crystallization of hydroxyapatite is not yet fully understood [5][6][7][8]. Some aspects of this problem were studied in this work.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, it is important that the CO 2 molecule can be inserted into the apatite lattice. This is the first report of a CA film with CO 2 molecules inserted without any hydroxy groups in the apatite skeleton; however, there are several reports on apatite crystals with both inserted CO 2 molecules and hydroxy groups [36][37][38][39].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the IR spectrum shows carbonate related absorption bands in two different frequency regions. Bands in the region between 1300 and 1650 cm À 1 are due to the v 3 (CO 3 ) stretching modes and the band at 873 cm À 1 reflects the v 2 (CO 3 ) bending vibration [36][37][38][39][40]. Previous work has suggested that the occupancy of the v 2 sites occurs competitively between the OH and carbonate groups, while that of the v 3 sites between phosphate and carbonate molecules [37,38,41].…”
Section: Co 3 Content In the Apatite Productmentioning
confidence: 99%